2020
DOI: 10.1097/rlu.0000000000003198
|View full text |Cite
|
Sign up to set email alerts
|

68Ga–Prostate-Specific Membrane Antigen PET–Positive Paget Bone Disease With Metastatic Prostatic Carcinoma

Abstract: Paget bone disease is a chronic benign bone disease characterized by excessive and abnormal bone remodeling. The scintigraphic and bone SPECT/CT hybrid imaging appearances of the affected bone(s) depend on the stage of the disease. We report the case of a patient newly diagnosed with prostate cancer who was found to have multiple osseous metastases, with coexisting Paget disease in the left hemipelvis diagnosed because of typical scintigraphic and SPECT/CT appearance. 68Ga–prostate-specific membrane antigen PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Bone is one of the most common sites of recurrence in prostate cancer 1 . 68 Ga-PSMA uptake by benign bone entities, including healing fractures, osteoarthritis, fibrous dysplasia, and Paget disease, has been documented, posing a diagnostic dilemma on 68 Ga-PSMA PET/CT and creating the potential for false-positive results 2–8 . The intense uptake in our patient’s SI joints is unusual as the intensity of PSMA uptake tends to be higher in malignant bone lesions than in benign pathologies, which usually demonstrate mild to moderate activity 9 .…”
mentioning
confidence: 74%
“…Bone is one of the most common sites of recurrence in prostate cancer 1 . 68 Ga-PSMA uptake by benign bone entities, including healing fractures, osteoarthritis, fibrous dysplasia, and Paget disease, has been documented, posing a diagnostic dilemma on 68 Ga-PSMA PET/CT and creating the potential for false-positive results 2–8 . The intense uptake in our patient’s SI joints is unusual as the intensity of PSMA uptake tends to be higher in malignant bone lesions than in benign pathologies, which usually demonstrate mild to moderate activity 9 .…”
mentioning
confidence: 74%
“…9,39 Additionally, ex vivo images of tumors and healthy organs harvested from mice 8 h post injection showed that 4WJ-X-EGFR apt nanoparticles strongly accumulated in tumors, with low or no accumulation in the liver or other organs. 5 Prostate-specific membrane antigen (PSMA) was detected in prostate cancer cells and the neovasculature of different kinds of malignant neoplasms, including breast, 429 brain, 430,431 lung, 430 and other cancers 432 but not in normal vascular endothelium. Our previous study demonstrated ligand− receptor binding of RNA nanoparticles with PSMA aptamers (Figure 30C) and PSMA-RNA nanoparticle displaying EVs.…”
Section: Rna Nanoparticles Functionalized With Targeting Groups As Ac...mentioning
confidence: 99%
“…Prostate-specific membrane antigen (PSMA) was detected in prostate cancer cells and the neovasculature of different kinds of malignant neoplasms, including breast, brain, , lung, and other cancers but not in normal vascular endothelium. Our previous study demonstrated ligand–receptor binding of RNA nanoparticles with PSMA aptamers (Figure C) and PSMA-RNA nanoparticle displaying EVs.…”
Section: Active Delivery Of Therapeutics By Rna Nanoparticles To Dise...mentioning
confidence: 99%
“…The prostate-specific antigen (PSA) was spotted in prostate cancer cells and the neovasculature of many types of malicious neoplasms, such as breast cancer [88], lung [89], and some other tumor cells [90]. One study reported ligand-receptor relation of RNA NPs with PSA aptamers.…”
Section: Prostate Cancermentioning
confidence: 99%